Development and gender equity : an uncompleted task - Nieves Rico, Maria (UN SantiagoCL, 1994)
Discusses the concept of gender as opposed to sex and analyses the efforts made to eliminate gender discrimination. Recognises the need for women to increase their participation at the political level, thus empowering them to make laws to remove discrimination. Suggests a redefinition of the division of labour and social roles to encompass equity of both genders.